Analisis Kondisi Keuangan Berdasarkan Rasio Likuiditas, Aktivitas dan Profitabilitas Pada Lembaga Perkreditan Desa (LPD) Desa Adat Kerobokan, Sawan - Ni Kadek Ayu Trisnadewi; Luh Eka Sri Sudeleni (ARTHA SATYA DHARMA, 2022)
The purpose of this study was to find out how the financial condition of the Village Credit Institution (LPD) of Kerobokan Traditional Village, Sawan in terms of Liquidity, Activity and Profitability aspects for the period 2015 to 2019. This study used a descriptive analysis approach. The type of data used is quantitative data. Data collection techniques in the form of documentation. The data analysis technique used in this research is the analysis technique of liquidity ratios, activity ratios, profitability ratios. The results showed that based on the analysis technique of LACLR, LDR, WTO and ROE, the financial condition of the Village Credit Institution (LPD) of the Traditional Village of Kerobokan, Sawan was categorized as healthy, this is because the ratio value obtained tends to be greater than the predetermined assessment standard. This condition shows good performance, while based on the analysis technique of RTO, TATO and ROA, the financial condition of the Village Credit Institution (LPD) of Kerobokan Traditional Village, Sawan is categorized as unhealthy, this is because the ratio value obtained tends to be smaller than the predetermined assessment standard. This condition shows poor performance.